(7+z)(3z-8)=0

Simple and best practice solution for (7+z)(3z-8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7+z)(3z-8)=0 equation:


Simplifying
(7 + z)(3z + -8) = 0

Reorder the terms:
(7 + z)(-8 + 3z) = 0

Multiply (7 + z) * (-8 + 3z)
(7(-8 + 3z) + z(-8 + 3z)) = 0
((-8 * 7 + 3z * 7) + z(-8 + 3z)) = 0
((-56 + 21z) + z(-8 + 3z)) = 0
(-56 + 21z + (-8 * z + 3z * z)) = 0
(-56 + 21z + (-8z + 3z2)) = 0

Combine like terms: 21z + -8z = 13z
(-56 + 13z + 3z2) = 0

Solving
-56 + 13z + 3z2 = 0

Solving for variable 'z'.

Factor a trinomial.
(-7 + -1z)(8 + -3z) = 0

Subproblem 1

Set the factor '(-7 + -1z)' equal to zero and attempt to solve: Simplifying -7 + -1z = 0 Solving -7 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1z = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1z = 0 + 7 -1z = 0 + 7 Combine like terms: 0 + 7 = 7 -1z = 7 Divide each side by '-1'. z = -7 Simplifying z = -7

Subproblem 2

Set the factor '(8 + -3z)' equal to zero and attempt to solve: Simplifying 8 + -3z = 0 Solving 8 + -3z = 0 Move all terms containing z to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -3z = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -3z = 0 + -8 -3z = 0 + -8 Combine like terms: 0 + -8 = -8 -3z = -8 Divide each side by '-3'. z = 2.666666667 Simplifying z = 2.666666667

Solution

z = {-7, 2.666666667}

See similar equations:

| -0.6+3.88=-0.8x+0.68 | | 5+2a=3a | | 13a+a^2+40=0 | | -9x-3=60 | | 27-4m=3 | | 6(2x+1)+2=2(4x+1)+2(2x+3) | | 9z-8z=5z+7+3z | | 0=16t^2+8+15 | | 40=(2x-1) | | 10x+5y=95 | | 9C=5F-160 | | -7a-10a= | | 4x+2=7x+7 | | -2x^2+10x-1=0 | | 3=z+6 | | 125w^6+27g^3=0 | | 3x^4-15x^2-72=0 | | 18x^2+15x=0 | | -20+7z+6z^2=0 | | 7x+15= | | 2x^2-7x=-6 | | 6t^2-96=0 | | 18x^2+21x=0 | | 7+2t+3t= | | -6wx^5(3w^6+4w^3x^4-9x^4)= | | 4a+12=3a+32 | | 13-2x=x^2-25 | | x^2+21=5 | | 7-2k=15 | | 6.7+12m-9.3=6.4 | | x^2+2=66 | | X+(x*1.25)=360000 |

Equations solver categories